PENGARUH TINGKAT PENGETAHUAN TERHADAP MINAT REMAJA PUTRI DENGAN METODE PENYULUHAN TENTANG PENCEGAHAN PRIMER KANKER SERVIKS DI SMAN 14 SURABAYA - DIAH ASTUTI, NIM011411231013 (2018)
Background: One of the most frequent diseases that affect the women's reproductive health is cervical cancer. Cervical cancer becomes the second largest type of malignant tumor in the world. Around 90% of the cervical cancers are caused by Human Pappiloma Virus (HPV). In this case, the teenage girls as the next future generationshould become the main concern. They need given a knowledge of the cervical cancer prevention in order to be able to maintain a healthy lifestyle. Methods: This study usesanexperimental research. Theresearch design of this study is the pre-experimental designs with one group pretestposttest design. This study also uses a total sampling. Furthermore, the dependent variable of this research is the teenage girl‟s interest. While the independent variable research is the level knowledge ofthe teenage girl. Moreover,the basis decision making in the study uses a Rank-spearman correlation test (rs). If the value Asymp.sig. (2-tailed) is smaller than <0.05, thus the Ha is accepted.Result: From the statistical test results, it obtained that p = 0.592 and r = 0.061. By the result of p = 0.592, it indicates that there is no correlation between the knowledge level towards the teenage girl‟s interest because p> 0,05. Whereas in the coefficient correlation value r = 0,061, it means that there is a positive correlation direction with the weak strength correlationbetween the variables tested. Thus, there is no influence on the level of knowledge towards the teenage girl‟s interest. Conclusion: In sum, this study has been shown that there is an increaseknowledge, but not all the improvements occur in the teenage girl‟s interest. Therefore, the knowledge level does not affect the teenage girl‟s interest in the primary prevention of cervical cancer. Keywords: Knowledge, Interests, Cervical Cancer